Analisis Kinerja Keuangan Anggaran Pendapatan Dan Belanja Daerah di Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jawa Barat - Kasan K. Suantha; Risma Yanti (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Local governments play an important role in improving the welfare of the community through effective and efficient financial management. The APBD functions not only as a financial plan but also as a financial performance measurement tool. However, the financial performance of local governments has not been optimal due to the imbalance between revenue and expenditure, low budget utilization efficiency, and inadequate financial management. This research uses a quantitative-descriptive approach without statistical data testing with data collection techniques in the form of interviews, observations, and documentation. Based on the research results, the effectiveness ratio of BPSDM West Java Province in 2021-2023 shows effective results with a percentage above 100%. The efficiency ratio is at an average level of 9.56%, which shows low efficiency or is categorized as less efficient. In addition, the activity ratio shows that operations are greater than investment expenditures, and the growth ratio shows very unstable, but shows strong potential for recovery if managed properly. The results of this study recommend BPSDM to improve the efficiency of budget management and prioritize spending on facilities and infrastructure that support public services. For future research, it is recommended to add research variables to measure financial performance more comprehensively and extend the research period to produce more accurate findings. This is important to support the improvement of the quality of public services in the future.